Strategi Branding Berbasis Kearifan Lokal dalam Pengembangan Objek Wisata Ranu Klakah - Muhammad Mughni Labib (Idarotuna : Journal of Administrative Science, 2025)
The purpose of this study is to examine local wisdom-based branding strategies used in the growth of the Ranu Klakah tourist destination in East Java's Lumajang Province.  Despite having substantial social and cultural potential, Ranu Klakah, one of the most well-liked tourist attractions, has not been successfully included in tourism promotion strategies.  This study combines a qualitative approach with a case study methodology.  Between 2020 and 2025, data was gathered through field observations, stakeholder interviews, and promotional media documents.  The research indicates that local identity, including customs, cultural values, and folklore, is not purposefully emphasized in destination branding. The site appears generic and fails to set itself apart from other natural attractions due to the visual style of contemporary promoting materials, which frequently lacks a distinctive cultural story.  Additionally, there is still little local community involvement in the branding process and irregular stakeholder coordination.  However, there is a great chance to mix digital branding with local knowledge stories through community empowerment and training in digital content.  This study recommends a branding strategy that highlights regional cultural identity, promotes community involvement, and cultivates enduring cross-sector cooperation.  With this approach, Ranu Klakah might develop into a destination with a strong cultural legacy that is genuine, competitive, and long-lasting.